Wave height and period on 16 March, 21 April, and 22 September 2019, in the Ujung Batee coastal waters and Lampanah coastal waters, Aceh Besar District, Indonesia. Issue 1 (November 2021) - Setiawan, I; Yuni, S M; Ulfah, M; Purnawan, S; Haridhi, H A; Masri, S R R; Muhammad, M; Ilhamsyah, Y
Abstract: Waves are one of the sea parameters that affect the rate of retreat of the coastline. This research investigation was carried out in the coastal waters of Ujong Batee and Lampanah, Aceh Besar District on 16 March, 21 April, and 22 September 2019, with the aim of examining wave parameters, namely wave height and period. Then the wave measurement data sampled at the research station location was carried out by purposive random sampling method. Sea wave data were taken using a scale board that has been labeled with numbers and a stopwatch. Wave measurements were carried out approximately 1000 times. Then the sea wave data is processed to obtain the wave height and period and then analyzed. The results obtained that the wave heights on 16 March, 21 April, and 22 September 2019 were 67 cm, 83 cm, and 80 cm in Ujong Batee and 55 cm, 67 cm, and 66 cm in Lampanah. While the wave period is 12 seconds on March 16, April 21, and September 22 in Ujong Batee and Lampanah. Thus, the wave height and period at both locations ranged from 50 cm to 80 cm and 12 s.